The Influence of Tax Avoidance and Institutional Ownership on Stock Prices with Dividend Policy as a Moderating Variable - I Ketut Wenten; Lailatul Khasanah (Jurnal Impresi Indonesia, 2025)
The purpose of this study is to determine the effect of tax avoidance and institutional ownership on stock prices with dividend policy as a moderator in companies operating in the non-cyclical customer sector for the 2019-2023 period partially. The research method uses a quantitative method. With a sample of 127 companies, the objects used are financial reports and annual reports for a period of 5 years. Data analysis uses classical assumption tests, regression analysis, coefficient of determination analysis, and coefficient of determination analysis using hypothesis testing. The results of this study are that tax avoidance has no partial effect on stock prices, the results of institutional ownership have no effect on stock prices, while using moderation tax avoidance and dividend policy mutually have no effect on stock prices and institutional ownership with dividend policy together produce significant results partially on stock prices.